2-Ene-1,4-diols by dimerization of terminal epoxides using hindered lithium amides. - Hodgson, D; Bray, C; Kindon, N (2005)
[reaction: see text] Reaction of hindered lithium amides with readily available (enantiopure) terminal epoxides gives 2-ene-1,4-diols via carbenoid dimerization of the corresponding alpha-lithiated epoxides. D-Mannitol and D-iditol were synthesized using this method in three steps from (S)-tritylglycidyl ether.